The Extraordinary Long-lasting Infrared Echo of PS16dtm Reveals an Extremely Energetic Nuclear Outburst - Ning Jiang; Di Luo; Jiazheng Zhu; Roc M. Cutri (The Astrophysical Journal Letters)
PS16dtm is one of the earliest reported tidal disruption events (TDEs) in active galactic nuclei and displays a remarkably bright and long-lived infrared (IR) echo revealed by multiepoch photometry from the Wide-field Infrared Survey Explorer (WISE). After a rapid rise in the first year, the echo remains persistently at a high state from 2017 July to 2024 July, the latest epoch, and keeps an almost constant color. We have fitted the extraordinary IR emission with a refined dust echo model by taking into account the dust sublimation process. The fitting suggests that an extremely giant dust structure with a new inner radius of ∼1.6 pc and an ultrahigh peak bolometric luminosity, i.e., ∼6 × 10 ^46 erg s ^−1 for typical 0.1 μ m-sized silicate grain, is required to account for the IR echo. This work highlights the distinctive value of IR echoes in measuring the accurate intrinsic bolometric luminosity and thus the total radiated energy of TDEs, which could be severely underestimated by traditional methods, i.e., probably by more than 1 order of magnitude in PS16dtm. Such large energetic output compared to normal TDEs could be boosted by the preexisting accretion disk and gas clouds around the black hole. Our model can be validated in the near future by IR time-domain surveys such as the Near-Earth Object Surveyor, given the recent retirement of WISE. In addition, the potential for spatially resolving a receding dusty torus after a TDE could also be an exciting subject in the era of advanced IR interferometry.